Yahoo Web Search

  1. 1 has two square roots... - 1 and 1 . That's how it works. Every positive number has negative and positive roots. (- 1 )*(- 1 ) = 1 and ( 1 )*( 1 ) = 1 .

    6 Answers · Science & Mathematics · 29/04/2008

  2. ∫ [ 1 / (x³ + 1 )] dx = first, you have..., it is factorable as: ∫ { 1 / [(x + 1 )(x² - x + 1 )]} dx = then decompose...break it up and factor out ( 1 /3): ( 1 /3) ∫ [ 1 /(x + 1 )] dx + ( 1 /3) ∫ [(- x + 2)/(x²...

    3 Answers · Science & Mathematics · 07/11/2008

  3. 1 ) -3x + 1 = - 1 - 2x 2) -3x (+ 3x ) + 1 = - 1 - 2x (+ 3x)--add 3x to each side 3) 1 = - 1 + x 4) 1 (+ 1 ) = - 1 (+ 1 ) + x--add 1 to each side 5) 2 = x The thing about these type problems is that you add or subtract variables...

    7 Answers · Science & Mathematics · 08/05/2008

  4. ∫( 1 +x^2)/( 1 +x)dx =∫( 1 +2x+x^2-2x)/( 1 +x)dx =∫((x+ 1 )^2-2x)/( 1 +x)dx =∫( 1 +x)dx - 2∫x/( 1 +x)dx =x+x^2/2 - 2∫x/( 1 +x)dx Let u= 1 +x. du=dx, x=u- 1 . =x+x^2/2 - 2∫(u- 1 )/udu =x+x^2/2 - 2[∫du...

    3 Answers · Science & Mathematics · 22/10/2014

  5. ∫ [ 1 /(secx - 1 )] dx = rearrange it as: ∫ { 1 /[( 1 /cosx) - 1 ]} dx = ∫ { 1 /[( 1 - cosx) /cosx]} dx = ∫ [cosx /( 1 ...(x/2)] /[2sin²(x/2)] dx = break it up into: ∫ ( 1 /2) [cos²(x/2) /sin²(x/2)] - ∫ ( 1 /2) [sin²...

    5 Answers · Science & Mathematics · 18/01/2009

  6. ( 1 /r + 1 /s)^- 1 Get a common denominator: [(s+r)/sr]^- 1 Take the reciprocal: sr/(s+r) In the numerator, get a common denominator: 1 /y+ 1 /y-y/y = (2-y)/y In the denominator, get a common denominator: 1 ...

    3 Answers · Science & Mathematics · 23/10/2011

  7. 1 + 1 = 2. why does it = 2? go and buy the principia mathimatica or download it. the first couple chapter explain why 1 + 1 = 2 its actually very interesting. with this book you can learn ALL of math.

    10 Answers · Science & Mathematics · 06/10/2009

  8. = 1 /(x- 1 )(x+0.5+0.5sqrt(3)i)(x+0.5-0.5sqrt(3)i) = A/(x- 1 ) + B/(x+0.5-0.5sqrt(3)i) + C/(x+0.5+0.5sqrt... (- 1 .5 - 0.5sqrt(3)i)(sqrt(3)i) = 1 so C = (- 1 .5 sqrt(3)i + 1 .5)^- 1 if x = -0.5+0.5sqrt(3)i, then...

    1 Answers · Science & Mathematics · 19/02/2009

  9. ( 1 / 7)^(- 1 ) = 7. A negative exponent is defined as a reciprocal so that it fits in with the rules for exponents, one of which is: x^a * x^b = x^(a + b). x^ 1 * x^(- 1 ) = x^0 = 1 Hence x^(- 1 ) = 1 / x.

    1 Answers · Education & Reference · 15/02/2010

  10. √( 1 - 3x) - 1 = x ==> √( 1 - 3x) = x + 1 ==> [√( 1 - 3x)]^2 = (x + 1 )^2 (Extraneous...x = 0 and x = -5 Check: -> x = 0 <- √[ 1 - 3(0)] - 1 = 0 ==> √( 1 - 0) - 1 = 0 ==> 1 - 1 = 0 ==> 0 = 0...

    3 Answers · Science & Mathematics · 05/06/2009

  1. Try asking your question on Yahoo Answers